Multimeric recombinant antibody (scFv) for ELISA detection of allergenic walnut: an alternative to animal antibodies - Madrid, Raquel; de la Cruz, Silvia; García-García, Aina; Alcocer, Marcos J.C.; González, Isabel; García, Teresa; Martín, Rosario (Elsevier, 2018)
Walnuts are classified as an important allergenic ingredient that can cause severe reactions in sensitized individuals. To prevent unintended exposure to products containing walnut, food manufacturers have the responsibility to declare its presence in packaged foods. Immunochemical methods are widely used to detect walnut proteins. However, available immunoassays rely on the use of antibodies raised in animals. In this work, an affinity probe for walnut proteins has been isolated from the Tomlinson I library, and further engineered in Pichia pastoris to produce the in vivo Juglans regia Biotinylated Soluble Fragment-single chain multimeric antibody (JrBSF-scFv). The multimeric scFv has been used to develop a direct enzyme-linked immunosorbent assay (ELISA), allowing detection of walnut in a food matrix with a limit of detection (LOD) of 1616 mg kg-1. This is the first recombinant antibody available for detection of walnut proteins. The assay is specific, only cross-reacting to some extent (2.25 %) to pecan, thus being useful as a screening tool for detection of walnut in raw or baked food matrices. Multimerization of the scFv with different avidin derivates could be of interest to improve sensitivity of the assay.